Thermodynamic assessment of the Fe-Nb-Si system - Jiang Y.; Li F.; Li S.-R.; Xu K.; Chen L.-L.; Deng X.-Z.; Huang Y.-Y.; Chang K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Nb–Si based alloys have drawn continuously increasing attention due to their excellent high-temperature mechanical properties. The addition of element Fe could improve their poor high-temperature oxidation resistance which largely restricts their application. With the aim to study the effect of Fe addition on the Nb–Si system and to design appropriate alloy composition, the Fe–Nb–Si ternary system was thermodynamically investigated using the CALPHAD (CALculation of PHAse Diagrams) approach aided with the formation enthalpies for ternary compounds at 0 K computed via ab initio calculations. A self-consistent thermodynamic description of the Fe–Nb–Si system was obtained in this work. Key isothermal sections and liquidus projection were presented, and the calculation results showed a good agreement with available experimental data.